Two new species in Hieracium sect. Umbrosa (Asteraceae) from Mt. Babia Góra, Western Carpathians, Poland - Szeląg, Zbigniew (Phytotaxa, 2025)
Two apomictic, stenoendemic species in Hieracium sect. Umbrosa are described from Mt. Babia Góra in the Western Carpathians, southern Poland: Hieracium stanislai (2n = 4x) which is similar morphologically to H. crepidifolium from the Alps, and H. walasii (2n = 3x) which differs in brownish-purple spotted leaves from all other representatives of the H. umbrosum agg. Both new species are illustrated with photographs of the holotypes and live plants in the type localities.